1989
DOI: 10.1093/jn/119.6.872
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cellulose Structure on Its Digestibility in the Rat

Abstract: The effect of modifying the structural properties of a purified cellulose on its subsequent digestion in the rat was determined. The three structurally unique types of cellulose used in the study were a commercial microcrystalline cellulose, a ball-milled cellulose, and an acid-swollen cellulose. The ball-milled cellulose and the acid-swollen cellulose were prepared from the microcrystalline cellulose starting material. Differences in structure between the types of cellulose were determined by X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…These results indicate that CEL may be, in small quantities, a substrate of SCFA production by intestinal bacteria. Explanation of this rising trend might be the report of Hsu and Penner (1989), where 5% inclusion of microcrystalline CEL to the diet led to its 8.8% digestibility, determined in rat faeces. Present study shows that the highest production of both total SCFA and butyrate was observed in the rats fed diets with 5% addition of FOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that CEL may be, in small quantities, a substrate of SCFA production by intestinal bacteria. Explanation of this rising trend might be the report of Hsu and Penner (1989), where 5% inclusion of microcrystalline CEL to the diet led to its 8.8% digestibility, determined in rat faeces. Present study shows that the highest production of both total SCFA and butyrate was observed in the rats fed diets with 5% addition of FOS.…”
Section: Discussionmentioning
confidence: 99%
“…A substance which is often used in animal experiments as the negative control is cellulose (CEL). However, it has been reported that CEL may affect intestinal absorption by increasing digesta viscosity (Takahashi et al, 2005), and its varied quantities can be fermented by bacteria in the large intestine of rats (Hsu and Penner, 1989;Juśkiewicz et al, 2005). For these reasons the recognition of CEL as an inert dietary component to the caecum is not obvious.…”
Section: Introductionmentioning
confidence: 99%
“…, 1999) and to alter the rheological profile of semi‐solid food systems, thus have a huge potential for novel food applications. Insoluble NSP, however, are regarded as having poor physical functionality (Hsu & Penner, 1989). Currently, the study on soluble NSP extraction is mainly focused on citrus peel (May, 1990; Kurita et al.…”
Section: Introductionmentioning
confidence: 99%
“…2±4 Amongst the properties of ®bre believed to in¯uence its physiological and nutritional effects are solubility, viscosity, hydration properties, particle size, fermentability and binding of organic compounds. 5,6 As pointed out by Hsu and Penner, 3 the mechanisms by which the chemical composition and physical structure of a ®bre affect its intestinal fermentation are important, because the extent of fermentation of a ®bre can modify its physiological effect. The effects of extensively fermentable ®bre are related to endproducts of fermentation (eg short-chain fatty acids), whereas the effects of poorly fermented ®bre depend more on the physical properties (eg water-holding capacity) of the ®bre itself.…”
Section: Introductionmentioning
confidence: 99%